First high–resolution analysis of the 2?1(A1) and interacting states of 72GeH4 and 73GeH4 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Koshelev M. A. Maksim Aleksandrovich; Velmuzhova I. A.; Sennikov P. G. Petr Gennadjevich; Bulanov A. D. Andrey Dmitrievich; Kuznetsov A. V. Alexey Valerevich; Leroy K. A. Klod Andre (2019, 2019)
Title screen